2017
DOI: 10.1080/13607863.2017.1421617
|View full text |Cite
|
Sign up to set email alerts
|

Using a therapeutic companion robot for dementia symptoms in long-term care: reflections from a cluster-RCT

Abstract: The findings suggest that one approach does not fit all, and that there is considerable variation in responses to PARO. A number of recommendations are discussed to aid the delivery of psychosocial interventions with PARO in practice, as well as to guide future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 37 publications
(34 reference statements)
2
85
0
1
Order By: Relevance
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
“…Positive behavioural responses were demonstrated through residents touching, petting, stroking, holding and hugging the robopet (Birks et al, ; Iacono & Marti, ; Jung et al, ; Moyle et al, , ). Visual responses (Birks et al, ; Gustafsson et al, ; Moyle et al, ) were often reported in terms of “alertness” and staff involved in a trial perceived that residents appeared to be more alert when they participated in activities with Paro (Moyle et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several studies began reporting the positive impact of SARs on the daily living and quality of life of older people . Many of these studies examined animal‐shaped companion robots and their therapeutic effects on older people . Takayanagi et al .…”
Section: Introductionmentioning
confidence: 99%